ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PADA JALAN POROS AP. MANGKUNEGARA STA 07+200 – STA 07+800 TENGGARONG SEBERANG - SAMARINDA - YUSUF, DEDE MOHAMMAD (KURVA S JURNAL MAHASISWA, 2020)
Traffic accidents are an indicator of the level of road safety. In developed countries, roads safety issues are of ectreme concern to reduce the number of traffic accidensts and the number of traffic accidents the occur. This is an indicator of the importance of understanding accident characteristics. This research discrusses the problem of traffic accidents thar occur in the city of Tenggarong. The purpose of this study was to determine the characteristic of traffic accidents. The results of this analysis methode get results of the cararteristics of the factors causing the accident such as the number of victims of the road such as Vertical Alignment, Visibility, LHR and Road Slope.